Investigation of the optical and electrical properties of dilute nitride compound semiconductors based on GaP - Albalawi, Hind Mohammed (2019)
The effect of nitrogen (N) incorporation on the optical properties of Gallium phosphide GaP1-xNx (x= 1.4%, 2.1%, and 2.7%) alloys grown by MBE, have been investigated in this thesis. In addition, the influence of adding arsnic (As) and indium (In) on the optical properties of GaAs0.1P0.89N0.01 and In0.07Ga0.93P0.99N0.01 alloys have been studied. The PL measurements demonstrated the change of the bandgap nature from indirect to pseudo-direct in all the above devices. PL intensity decreased with increasing N concentrations as well as the bandgap energy. GaAs0.1P0.89N0.01 alloy has shown better PL intensity, FWHM and reached the target bandgap of solar cells materials based on Si substrate which is 1.8 eV compared to In0.07Ga0.93P0.99N0.01 alloy. Furthermore, the effect of different epilayer thickness (100 nm and 1 μm) on the optical properties of GaAs0.1P0.89N0.01 alloys have been studied. Increasing the thickness allowed to enhance the optical efficiency by increasing the PL intensity, reducing the FWHM and raising the activation energy. However, the bandgap shifted towards higher energy (higher than 1.8 eV) Also in this thesis, the effect of RTA on the optical and structural properties of GaP0.986N0.014, GaAs0.1P0.89N0.01 and In0.07Ga0.93P0.99N0.01 devices have been examined. From an optical point of view, all samples had a blue shift in their bandgap energy after annealing. It increased also the PL intensities as well as the activation energies for all alloys. The S-shape behaviour was not affected much by annealing these materials. However, the FWHM showed smaller values after annealing the samples, indicating that RTA reduced the defects. From a structural per-spective, RTA decreased the surface roughness of GaP0.986N0.014, however, no change in N-induced in vertical lattice spacing was observed. A small reduction of vertical lattice parame-ter and an increase of the surface roughness were caused by annealing for both GaAs0.1P0.89N0.01 and In0.07Ga0.93P0.99N0.01 alloys. Moreover, I-V, C-V, DLTS, and Laplace DLTS measurement techniques were used to investigate the effect of RTA on the electrical properties of p-i-n GaAsPN solar structure materials grown by MBE. This study showed a noticeable effect of annealing on the samples and was correlated to the creation of new defects. RTA improved the electrical properties of this material by reducing the concentration and /or capture cross-section values of major defects. Overall, rapid thermal annealing is an effective treatment process to improve the optical, structural and electrical properties of different semiconductor structures and devices.